5.4.36 Problems 3501 to 3600

Table 5.485: Second ODE homogeneous ODE

#

ODE

Mathematica

Maple

17988

\[ {}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0 \]

17991

\[ {}{y^{\prime \prime }}^{2}+2 x y^{\prime \prime }-y^{\prime } = 0 \]

17992

\[ {}{y^{\prime \prime }}^{2}-2 x y^{\prime \prime }-y^{\prime } = 0 \]

17995

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+n \left (n +1\right ) y = 0 \]

17996

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}+y = 0 \]

17997

\[ {}\sin \left (x \right )^{2} y^{\prime \prime } = 2 y \]

18005

\[ {}y^{\prime \prime }+y = 0 \]

18007

\[ {}y^{\prime \prime }+p_{1} y^{\prime }+p_{2} y = 0 \]

18008

\[ {}\left (2 x +1\right ) y^{\prime \prime }+\left (4 x -2\right ) y^{\prime }-8 y = 0 \]

18009

\[ {}\sin \left (x \right )^{2} y^{\prime \prime }+\cos \left (x \right ) \sin \left (x \right ) y^{\prime } = y \]

18014

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

18026

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}-\frac {n \left (n +1\right ) y}{x^{2}} = 0 \]

18032

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}+\left (1-\frac {m^{2}}{x^{2}}\right ) y = 0 \]

18033

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}+y = 0 \]

18034

\[ {}y^{\prime \prime }+\frac {2 p y^{\prime }}{x}+y = 0 \]

18035

\[ {}x y^{\prime \prime }-y^{\prime }-x^{3} y = 0 \]

18037

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{\sqrt {x}}+\frac {y \left (-8+\sqrt {x}+x \right )}{4 x^{2}} = 0 \]

18044

\[ {}y^{\prime \prime }+2 y^{\prime }+y^{2} = 0 \]

18060

\[ {}y^{\prime \prime }+4 y = 0 \]

18061

\[ {}y^{\prime \prime }-4 y = 0 \]

18101

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

18187

\[ {}y y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

18188

\[ {}x y^{\prime \prime } = y^{\prime }+{y^{\prime }}^{3} \]

18189

\[ {}y^{\prime \prime }-k y = 0 \]

18190

\[ {}x^{2} y^{\prime \prime } = 2 x y^{\prime }+{y^{\prime }}^{2} \]

18192

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = 0 \]

18194

\[ {}\left (x^{2}+2 y^{\prime }\right ) y^{\prime \prime }+2 x y^{\prime } = 0 \]

18195

\[ {}y y^{\prime \prime } = y^{\prime } y^{2}+{y^{\prime }}^{2} \]

18196

\[ {}y^{\prime \prime } = y^{\prime } {\mathrm e}^{y} \]

18199

\[ {}y y^{\prime \prime } = {y^{\prime }}^{2} \]

18205

\[ {}y y^{\prime \prime }+{y^{\prime }}^{2}-2 y y^{\prime } = 0 \]

18209

\[ {}y^{\prime \prime }+2 x {y^{\prime }}^{2} = 0 \]

18221

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime } = 0 \]

18233

\[ {}x^{2} y^{\prime \prime } = y^{\prime } \left (3 x -2 y^{\prime }\right ) \]

18239

\[ {}y^{2} y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

18244

\[ {}x^{2} y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

18247

\[ {}y^{\prime \prime } = 2 y {y^{\prime }}^{3} \]

18250

\[ {}x y^{\prime \prime }+y^{\prime } = 0 \]

18258

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

18260

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }-5 y = 0 \]

18261

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (x^{2}+6\right ) y = 0 \]

18262

\[ {}y^{\prime \prime }-y = 0 \]

18263

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

18264

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

18265

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

18266

\[ {}x^{2} y^{\prime \prime }-2 y = 0 \]

18267

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

18268

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

18269

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

18270

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

18271

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

18272

\[ {}y^{\prime \prime }+y = 0 \]

18273

\[ {}y^{\prime \prime }-y = 0 \]

18274

\[ {}x y^{\prime \prime }+3 y^{\prime } = 0 \]

18275

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

18276

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

18277

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

18278

\[ {}y^{\prime \prime }-\frac {x y^{\prime }}{x -1}+\frac {y}{x -1} = 0 \]

18279

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

18280

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

18281

\[ {}y^{\prime \prime }-x f \left (x \right ) y^{\prime }+f \left (x \right ) y = 0 \]

18282

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

18283

\[ {}x y^{\prime \prime }-\left (x +n \right ) y^{\prime }+n y = 0 \]

18284

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

18285

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

18286

\[ {}x y^{\prime \prime }-\left (x +3\right ) y^{\prime }+3 y = 0 \]

18287

\[ {}y^{\prime \prime }-f \left (x \right ) y^{\prime }+\left (f \left (x \right )-1\right ) y = 0 \]

18288

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

18289

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

18290

\[ {}y^{\prime \prime }+8 y = 0 \]

18291

\[ {}2 y^{\prime \prime }-4 y^{\prime }+8 y = 0 \]

18292

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

18293

\[ {}y^{\prime \prime }-9 y^{\prime }+20 y = 0 \]

18294

\[ {}2 y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

18295

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

18296

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

18297

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

18298

\[ {}4 y^{\prime \prime }+20 y^{\prime }+25 y = 0 \]

18299

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

18300

\[ {}y^{\prime \prime } = 4 y \]

18301

\[ {}4 y^{\prime \prime }-8 y^{\prime }+7 y = 0 \]

18302

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

18303

\[ {}16 y^{\prime \prime }-8 y^{\prime }+y = 0 \]

18304

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

18305

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 0 \]

18306

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

18307

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

18308

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

18309

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

18310

\[ {}y^{\prime \prime }+4 y^{\prime }+2 y = 0 \]

18311

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

18312

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+10 y = 0 \]

18313

\[ {}2 x^{2} y^{\prime \prime }+10 x y^{\prime }+8 y = 0 \]

18314

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-12 y = 0 \]

18315

\[ {}4 x^{2} y^{\prime \prime }-3 y = 0 \]

18316

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

18317

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 0 \]

18318

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }+3 y = 0 \]

18319

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

18320

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-16 y = 0 \]